2019
DOI: 10.1063/1.5094324
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Lyapunov exponents beyond continuous measurements

Abstract: Quantum systems, when interacting with their environments, may exhibit non-equilibrium states that are tempting to be interpreted as quantum analogs of chaotic attractors. However, different from the Hamiltonian case, the toolbox for quantifying dissipative quantum chaos remains limited. In particular, quantum generalizations of Lyapunov exponents, the main quantifiers of classical chaos, are established only within the framework of continuous measurements. We propose an alternative generalization based on the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 64 publications
1
11
0
Order By: Relevance
“…To calculate the largest Lyapunov exponent (LE), we use the recently developed method based on a parallel evolution of fiducial and auxiliary trajectories, ψ f (t) and ψ a (t), under Eq. ( 5) 12 , in the spirit of the classical LE ideology 26 . The distance between the trajectories is calculated as the absolute difference between the two corresponding observables θ .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To calculate the largest Lyapunov exponent (LE), we use the recently developed method based on a parallel evolution of fiducial and auxiliary trajectories, ψ f (t) and ψ a (t), under Eq. ( 5) 12 , in the spirit of the classical LE ideology 26 . The distance between the trajectories is calculated as the absolute difference between the two corresponding observables θ .…”
Section: Methodsmentioning
confidence: 99%
“…In our recent work 17 we showed that a photonic mode of an open and periodically modulated Kerr-nonlinear cavity can exhibit transitions from regular dynamics to chaos. A degree of chaos is quantified with quantum Lyapunov exponent 12 . These transitions are also associated with modification of the probability distribution of photon emission waiting times, which changes its intermediate asymptotic from the exponential (regular dynamics) to a power-law (chaos) decay.…”
Section: Introductionmentioning
confidence: 99%
“…( 4), is initiated again, until the next quantum jump occurs, etc. The largest quantum Lyapunov exponent 8 is calculated as the average rate of exponential growth of the distance between the base ψ b (t) and perturbed ψ v (t) quantum trajectories that evolve according to the Eq. ( 4), in full analogy with the classical definition 23 .…”
Section: B Quantum Lyapunov Exponentmentioning
confidence: 99%
“…In our recent works [8][9][10] , we proposed an alternative way to quantify the degree of chaos in the evolution determined by Lindbladian L . Namely, we introduced a quantum version of Lyapunov exponents (LEs) which is based on the idea of unraveling the master equation, Eqs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation